Hubungan Struktur Modal, Kinerja Perusahaan dan Harga Saham pada Perusahaan Property dan Real Estate yang Listed di Bursa Efek Indonesia - Tendian Afriano; Nikmah Nikmah (Jurnal Akuntansi, 2016)
The purpose of this research was to examine the influence of direct capital structure towards the company's performance and stock price and test the influence of indirect capital structure towards the price of the stock on the company's financial performance through property and real estate were listed on the Indonesia stock exchange in 2009-2014. This research uses the Partial Least Square approach (PLS). The sample consisted of 38 companies research property and real estate registered in BEI in 2009 until 2014. Sampling done by the method of purposive sampling. The results of this research are proving there is a direct positive influence on performance of capital structure of the company, a positive performance against direct influence stock prices and indirectly influence modal structure against the stock price through the company's performance, but this research did not manage to prove direct influence the structure of the capital against the stock price. The results obtained in the research contributes important for firms in the capital structure decision making optmal.Keywords: Capital Structure, Company Performance, Stock Price